Characterising the epigenetic architecture of differential treatment outcomes in a South African first-episode schizophrenia cohort with emphasis on miRNA-mediated regulation - Jooste, Sarel Christiaan (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.